2019
DOI: 10.1136/bcr-2018-227876
|View full text |Cite
|
Sign up to set email alerts
|

“Fungating” tumour? No, it’s bacterial!

Abstract: A fit and healthy 26-year-old woman presented to the general surgical team with epigastric pain and weight loss of 2 stones over 6 months. She has also a positive family history of ulcerative colitis. As her oesophagogastroduodenoscopy and colonoscopy were normal, a contrasted CT was requested, and it detected an inflammatory mass with fat streaking around her transverse colon. An intrauterine contraceptive device (IUCD) was noted. In light of the CT findings, she underwent a diagnostic laparoscopy. As the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Renal, gallbladder and biliary tract [23], pancreas, stomach, small intestine, and omental actinomycosis cases have also been reported [24][25][26]. Mesenteric actinomycosis is extremely rare, with very few reports in the literature, and usually presents as a mesenchymal mesenteric tumor with non-specific characteristics [4]. Chan et al described the case of a 45-year-old man with abdominal pain, whose CT image revealed a mesentery-limited actinomycotic abscess without extension to surrounding tissue, except for the accompanying inflammation of the appendiceal tip [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal, gallbladder and biliary tract [23], pancreas, stomach, small intestine, and omental actinomycosis cases have also been reported [24][25][26]. Mesenteric actinomycosis is extremely rare, with very few reports in the literature, and usually presents as a mesenchymal mesenteric tumor with non-specific characteristics [4]. Chan et al described the case of a 45-year-old man with abdominal pain, whose CT image revealed a mesentery-limited actinomycotic abscess without extension to surrounding tissue, except for the accompanying inflammation of the appendiceal tip [20].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the body system affected, actinomycosis can be classified as oro-cervico-facial, thoracic or abdominopelvic disease. The involvement of other body regions leads to symptoms from the central nervous system (CNS), the cardiovascular system, the musculoskeletal system, the urinary system, and the skin [ 3 , 4 ]. Lately, a decreasing incidence of the oro-cervico-facial type of actinomycosis has been reported, whereas abdominal and pelvic infections are increasing, mainly due to the use of intrauterine contraceptive devices (IUCD) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%